Species heights of Siberian spruce on the Yenisei Ridge - Shevelev Sergey; Mikhaylov Pavel; Vorobeva Irina; Vais Andrey; Romanova Larisa; Artemyev Oleg; Nemich Victor (E3S Web of Conferences, 2024)
The work is based on materials from 15 sample plots laid out in mixed spruce stands of the Yenisei Ridge, with a relative completeness in the range of 1.62-1.27, belonging to the green moss group of forest types. Based on the data obtained, the features of changes in spruce species heights and their interdependence with other taxation characteristics were established. The results of data processing indicate the need to develop a set of taxation standards for the Yenisei Ridge region.